Decision making to manage the optimal selection of personnel in the hotel company applying the hungarian algorithm - Anna María Gil-Lafuente; Young Kyun Oh (The International Journal of Management Science and Information Technology (IJMSIT), 2012)
In a context of globalization and permanent change, we present a process for the administration and the management of human resource in the field of the organization of the hotel environment. The classic systems used for the optimal selection of personnel among the proposed candidates are often ineffective due to the existence of variables (characteristics, peculiarities or singularities) not only objective but also mostly subjective. We have proposed the application of a model based on the treatment of uncertainty, the Hungarian Algorithm (also known as König's Algorithm), in order to show a process for optimal selection of personnel. This work allows for a company, in hotel business, can choose those candidates who will be best fit for the offered jobs, but at the same time optimizing the candidates' aptitude in the set of hotel atmosphere. The objective is to see how candidates are as efficient as possible to the company, and not only analyzing the individual efficiency of each jobs.
Keywords: 650; decision making; Hungarian Algorithm; human resources; selection of personnel; hospitality